Low Vision Management For Infantile Nystagmus: A Case Study. - Troy, Alexandra; Appel, Sarah (Optometry & Visual Performance, 2015)
Background: Infantile nystagmus is a common cause of visual impairment. It can occur in isolation, but it is often found in association with other conditions, such as albinism. The condition results in varying levels of vision impairments ranging from mild to severe. Characteristics include early onset, bilateral involvement, pendular and jerk waveforms, the presence of a null point, and the lack of optokinetic nystagmus and oscillopsia (environment moving). This article provides a review of pathogenesis, epidemiology, and treatment of infantile nystagmus. A case study highlights low vision strategies and management for the condition. Case Report: A 12-year-old male with infantile nystagmus presented to the satellite low vision pediatric clinic for initial evaluation. He reported difficulty with different tasks at school secondary to his visual impairment. Low vision intervention utilized various devices and strategies to meet his distance and near goals. Discussion: With no known cure, low vision rehabilitation is important for individuals with nystagmus to allow them to reach their highest potential. Rehabilitation techniques can easily be applied by a primary care optometrist.